A case-crossover analysis of air pollution and mortality in Philadelphia. - Neas, L M (1999)
This study reassessed Schwartz and Dockery's analysis of daily mortality from nonexternal causes among residents of Philadelphia, Pennsylvania, over 8 years, from 1973 to 1980 [American Review of Respiratory Disease 145:600-604 (1992)]. A Poisson regression analysis using the same model found that a 100-microg/m(3) increment in the 48-hr mean concentration of total suspended particulates (TSP) was associated with increased all-cause mortality [rate ratio = 1.069; 95% confidence interval (CI), 1.043-1.096) after adjustment for quadratic trend, season, year, previous day's mean temperature, dew point, winter temperature, and indicators of hot (temperature > 80 degrees F) and humid days (dew point > 66 degrees F). Critics suggested that time-varying factors such as season and day of week were not sufficiently controlled in this analysis and subsequent studies in other locations. We used a conditional logistic regression analysis with a case-crossover design to reanalyze the data, with air pollution in the prior and subsequent weeks to the day of death serving as referent periods. The case-crossover approach controls for season and day of week by design rather than modeling. We found that a 100-microg/m(3) increment in the 48-hr mean level of TSP was associated with increased all-cause mortality [odds ratio (OR) = 1.056; CI, 1.027-1.086) after adjustment for the same weather variables as above. Similar associations were observed for deaths in individuals over 65 years of age (OR = 1.074; CI, 1. 037-1.111) and for deaths due to cardiovascular disease (OR = 1.063; CI, 1.021-1.107). The current case-crossover analysis confirms the general conclusion of the previous Poisson regression analysis of an association of TSP with daily mortality in Philadelphia, Pennsylvania.